EUDAIMONIC WELL-BEING ACTIVITY: FULFILLMENT OF BASIC PSYCHOLOGICAL NEEDS AND SUBJECTIVE WELL-BEING IN ADOLESCENTS - Hidayatul Fikra; Fitri Ariyanti Abidin (Jurnal RAP (Riset Aktual Psikologi Universitas Negeri Padang), 2024)
The adolescent phase is a vulnerable period in human life because it is a transition period from childhood to adulthood. In this phase, good subjective well-being is needed so that adolescents can fulfill their developmental tasks. One of the efforts to fulfill subjective well-being is through adolescent eudaimonic activities that refer to three components of basic psychological needs, namely the need to be independent, the need to be competent and the need to connect with others. The purpose of this study is to analyze eudaimonic activities that meet the three components of basic psychological needs and subjective well-being. This study used a concurrent mixed method approach with four qualitative questions and the SPANE and BPNFS scales. The results showed there were 21 eudaimonic activities grouped into six activity categories, namely physical activities, entertainment, skills, spiritual, learning and favorite habits. This study recommends further research with explorative methods and a larger sample size. As an implication for adolescent life, parents or families can study eudaimonic activities in adolescents so that the approach and supervision given to adolescents becomes more appropriate.